Pemesanan Hewan Dengan Sampel Analisis Pemikiran Imam Abu Hanifah dan Imam Syafi’i - Achmad Nursobah; Imam Turmudi; Azis Ahmad Nurhali (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The aim of this research is to describe the thoughts of Imam Abu Hanifah and Imam Syafi'i regarding ordering animals with samples. Here we will explain the thoughts of Imam Abu Hanifah and Imam Syafi'i regarding ordering animals by sample, namely by replacing the mention of the nature, type and everything related to the animal with a sample of the animal provided by the seller. The research method in this research is library research by taking references from the books by Imam Abu Hanifah and Imam Syafi'i contained in the book Badāi'u ash-Sana'i Fi Tartib as-Syarā'i by Imam as-Syarkhasi and al-Umm by Imām Syāfi'i and other books that support discussion material as well as other materials such as data sources for books, articles, papers, journals and so on. The result of this discussion is that ordering animals with samples is permitted because this includes the practice of greeting contracts. It is permissible if you fulfill the four additional conditions included in the terms of the goods, because this is a contract of relief (rukhsoh) then some of these conditions cannot be ignored. Imām Syāfi'i based this on hadith and qiyas-an on debts, based on a hadith from Abu Rafi ' which explains the Prophet borrowed a camel, and replaced it with a better one. Meanwhile, Imam Abu Hanifah's opinion does not allow basing it on hadith and istihsan bil maslahah.